Perception of flood hazard and coping strategies of selected families in Brgy. Bagong Silangan, Quezon City - Araquil, Sharelee D.; Gabriel, Florenda S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
This study described flood and flood hazards as perceived by the households; identified disaster preparation and coping strategies of households before, during, and after flood; and determined the relationship of household characteristics to perception of flood, perceived level of preparedness and satisfaction with disaster preparation and coping strategies of the households. Data were gathered through field survey of 50 households residing in frequently flooded areas of Barangay Bagong Silangan, Quezon City. Situated in the most susceptible part of the Marikina flood plain, the respondents experience an average of 15 flood events every year. Results show that households normally experience flood as low as ankle level and as high as above the house with floodwaters which generally subside within the day. These households had disaster preparations that were practiced to protect basic needs like food and clothes. Coping strategies that were performed frequently differ throughout the flood period - coping strategies on food is given high importance before the flood, personal safety and mobility during the flood, and house and surroundings after the flood. Coping strategies on information and community participation were frequently employed throughout the flood occurrence. These coping strategies frequently employed before, during, and after flood reflect the protection of the crucial basic needs and resources of households relevant for each period. Low-income households showed more positive perception to overcoming flood hazards while households living in the higher parts of the area were more prepared and satisfied with their preparations. Furthermore, family composition showed significant relationships with various coping strategies.
Thesis Classification: F
Thesis (B.S. Home Economics)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Emergency management -- Philippines -- Quezon City